축산 농가의 악취 제어를 위한 악취물질 22종의 빅데이터 분석 - 신동철(Dong chul Shin) (Daehan hwan'gyeong gonghag hoeji, 2024)
목적:본 연구에서는 악취 발생 특성과 추세를 파악하기 위해 1년 동안 축산 농가에서 22가지 화합물에 대한 연속(20분 간격) 측정 데이터를 수집하여 빅데이터 분석을 통해 악취 농도와 풍향 및 풍속, 온도, 습도 등의 환경 요인 간의 관계를 분석하였다. 방법:측정 물질은 한국 환경부에서 ‘지정 악취 물질’로 정의한 22가지 화합물이었습니다. 검출 및 농도 측정은 두 종류의 컬럼(VB-WAX 및 VB-1)과 검출기(FID 및 PID)를 사용하여 가스크로마토그래피로 수행되었다. 샘플링은 2분 ~ 5분마다 수행되었고 열 탈착 후 크로마토그래피에 주입하였다. 분석에서 얻은 데이터는 2022년 8월 1일부터 2023년 7월 31일까지 온도, 습도, 풍속 및 풍향과 같은 환경 변수와 함께 저장되었습니다. 총 측정 데이터 수는 26,280개이다. 결과 및 토의:상관 분석 결과 온도는 디메틸디설파이드, 이소발레르알데히드와 상관 관계가 있었고 습도는 톨루엔, 이소부틸알코올, 트리메틸아민과 상관 관계가 있었다. 6가지 주성분이 총 분산의 60.7%를 설명했으며, 2가지 주성분인 PC 1과 PC 2를 선택하여 분석했다. PC 1은 휘발성 유기 화합물과 강하게 연관되었고 PC 2는 산성 화합물과 연관되었다. 양극성 플롯 결과와 함께 PC 1은 휘발성 특성으로, PC 2는 산성 특성으로 각각 정의되었다. 주성분을 종속 변수로, 환경 변수를 독립 변수로 한 다중 회귀 분석은 PC 1을 제외하고 조정된 R2 값이 0.539로 비교적 작았다. 결론:악취가 나는 화합물은 유사한 분자적 특성으로 확산되고 함께 이동하는 경향이 있어 검출된 농도 패턴이 유사했다. PC 1은 다중 회귀 분석을 통해 환경 변수와 상관 관계가 있었지만, 화합물의 특성이 온도, 습도 및 바람에 따라 달라지기 때문에 설명할 수 있다. Objectives:This research collected continuous (20-minute interval) measurement data of 22 compounds from cattle farms during a year in order to understand malodor emission characteristics and trends and also big data analysis was performed to analyze the relationships between malodor concentration and environmental factors such as wind direction and speed, temperature, and humidity. Methods:The measured substances were 22 compounds defined as ‘designated malodor-producing substances’ by Korean Ministry of Environment. Detection and concentration measurement were performed by gas chromatography with two kinds of columns (VB-WAX, and VB-1), and detectors (FID and PID). Sampling was carried out with pumping every 2 or 5 minute and thermal desorption was followed by chromatograph injection. Data obtained from analysis were stored with environmental variables such as temperature, humidity, wind speed, and wind direction from 1 August 2022 to 31 July 2023. Total number of measurement data was 26,280. Results and Discussion:Correlation analysis showed that temperature was correlated with dimethyl disulfide, and iso-valeraldehyde, and humidity was correlated with toluene, iso-butylalcohol, and trimethylamine. Six principal components explained 60.7% of total variance and two principal components, PC 1 and PC 2, were selected and analyzed. PC 1 was strongly related with volatile organic compounds and PC 2 was related with acid compounds. Together with bipolar plot results, PC 1 was defined as volatile properties and PC 2 as acidic characteristics, respectively. Multiple regression with principal components as dependent variables and environmental variables as independent showed relatively small value of adjusted R2 except PC 1 of 0.539. Conclusion:Malodorous compounds tended to diffuse and move together with similar molecular characteristics which made the detected concentration similar in patterns. Though PC 1 had correlation with environmental variables through multiple regression analysis, it can be explained as chemical compound’s characteristics depends on temperature, humidity, and wind. KCI Citation Count: 0